Responding to the Irish Government's Announcement on the New Access and Work Scheme. A Human Rights Approach - Leeson, Lorraine; Conama, John (My University, 2025)
Ireland continues to fail to uphold the human rights of deaf people. On 30th July 2024, Minister for social Protection launched the new Work and access Programme, which offers a set of supports to people with disabilities to obtain a job or remain in work. the aim is to remove or reduce barriers in the workplace for people with a disability. however, as this article aims to highlight, there are two issues of concern within the Work and access scheme for deaf people that need to be addressed: the perception of irish sign language (isl) as a form of ‘communication support’ and the cap in number of hours of support available for deaf isl users. this paper aims to show why these concerns will have a negative impact on deaf people’s ability to participate in the workplace and to offer suggestions for how these might be alleviated.
PUBLISHED
Keywords: Inclusive Society; Making Ireland; Deaf Studies; Irish Sign Language Interpreting; sign language interpreting